(untitled) (Praxis Educativa, 2012)
This papers inform on investigations advances in the comprehension of school dynamics, it’s dramatics nucleus and the organization that is putting to work due to social situations in critical conditions, through on analysis comparing cases between different schools that belong at the same geographic area.